THE RELATIONSHIP OF CHILDREN KNOWLEDGE THROUGH 4 HEALTHY 5 PERFECT FOOD TOWARD UNDER HEALTH SERVICES IN SCHOOL: HUBUNGAN TINGKAT PENGETAHUAN MAKANAN 4 SEHAT 5 SEMPURNA DENGAN SIKAP ANAK TERHADAP JAJANAN TIDAK SEHAT PADA ANAK SEKOLAH - Rani Devayanti; Agus Triwinarto (Wijaya Husada, 2018)
Food is most important needs for human being, by consuming a food every human can be live, growing and thinking. Intensely of food is affecting bodies as well as minds. If we consume dirty and unhealthy food then the condition of the agency can to deteriorate so it can be cause the disease. However, if we consume too much food, what else are instantly made a preservative can result in the performance of the brain being broken, slow in thinking something, and lost of concentration. The aim of this research is to find out the relationship of children knowledge through 4 healthy 5 perfect foods toward under health services in 5 grade of Mardiyuana Elementary School. The design of this research is analytic approach description on the cross sectional research. To conudct this research, the researcher collect the data by using questionnaire, only 100 with the statistics chi square. The collection of data were collected from the spread of the questionnaire covered. The results of this research is the son of having knowledge of good as many as 49 or ( 49 percent from 100 respondents , and children with positive attitude as many as 62ofrespondentsor(62%).ThestatisticsoftheresultsobtainedPv0.030and0.05 then Pv <,So Ho rejected whichmeans there is a level of knowledge of healthy food 4 5 perfect with the attitude of children against unhealthy snacks.